2021
DOI: 10.1371/journal.pone.0247980
|View full text |Cite
|
Sign up to set email alerts
|

Association between meteorological factors and the prevalence dynamics of Japanese encephalitis

Abstract: Japanese encephalitis (JE) is an acute infectious disease caused by the Japanese encephalitis virus (JEV) and is transmitted by mosquitoes. Meteorological conditions are known to play a pivotal role in the spread of JEV. In this study, a zero-inflated generalised additive model and a long short-term memory model were used to assess the relationship between the meteorological factors and population density of Culex tritaeniorhynchus as well as the incidence of JE and to predict the prevalence dynamics of JE, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
(20 reference statements)
0
14
0
2
Order By: Relevance
“…Japanese encephalitis (JE), a serious vector-borne viral infection caused by the Japanese encephalitis virus (JEV), is responsible for causing Epidemic encephalitis B—an acute infectious disease of the central nervous system, in 24 countries of Southeast Asia and the Western Pacific 1 3 . As the transmission of JE is highly dynamic, several studies have reported substantial variation in the estimation of its global impact.…”
Section: Introductionmentioning
confidence: 99%
“…Japanese encephalitis (JE), a serious vector-borne viral infection caused by the Japanese encephalitis virus (JEV), is responsible for causing Epidemic encephalitis B—an acute infectious disease of the central nervous system, in 24 countries of Southeast Asia and the Western Pacific 1 3 . As the transmission of JE is highly dynamic, several studies have reported substantial variation in the estimation of its global impact.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we applied the Dropout method to examine the uncertainty of 1- to 12-week ahead LSTM models, which has been used in estimating the uncertainty of LSTM-based disease risk prediction [ 38 ]. Specifically, based on the fixed parameters of LSTM and the testing set, we outputted 50 predictions by dropping a fixed percent of units randomly and computed the maximum, minimum, and mean of 50 predicted values for each epi week to generate the predicted interval.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty years ago, approximately 75% of JE patients were children aged 0-14 years, whereas adults were generally considered immune because they had experienced at least one natural infection [2]. The JE fatality rate is 20-30%, and 30-50% of survivors suffer from permanent and irreversible neuropsychiatric sequelae, which have placed a heavy burden on the public health system and society [3]. Therefore, JE has become a public health issue of international concern [4].…”
Section: Introductionmentioning
confidence: 99%